EVALUASI PEMBELAJARAN SECARA DARING PADA MASA PANDEMI COVID 19 DI PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR STKIP PGRI BANDAR LAMPUNG - Supriyono, Supriyono; Sutrisno AB, Joko; Saputra, Fredi Chandra (Lentera: Jurnal Ilmiah Kependidikan, 2020)
This study aims to describe the evaluation of learning during the Covid-19 pandemic at STKIP PGRI Bandar Lampung and the problems faced. This research is a quantitative descriptive study with a survey method conducted online. Primary data collection was carried out by distributing online questionnaires to 133 respondents of Elementary School Teacher Education students who experienced the impact of the Covid-19 Pandemic. In addition, supporting data with secondary data, namely documents, news, and articles related to online learning during the Covid-19 Pandemic. The results showed that the independent learning system seemed forced so that it made students feel bored quickly. For this reason, guidance is needed to foster the process of student learning independence, namely through positive discipline. The weakness in online learning is the lack of maximum student involvement.